Prácticas de alimentación complementaria y su relación con la prevalencia de desnutrición en lactantes mayores de 12 a 24 meses atendidos en el Centro de Salud Atarazana octubre 2024 – mayo 2025. - Manzo Loor, Joely Paola (2025)
Complementary feeding is the beginning of the intake of foods other than breast milk and infant milk formulas, with the objective of completing the energy needs as well as macro and micronutrients, which these are not able to provide. The general objective of the research is to determine the impact of complementary feeding practices on the prevalence of malnutrition in infants aged 12 to 24 months attended at the Atarazana Health Center, during October 2024 to May 2025. Therefore, using a quantitative approach, data were collected through surveys applied to caregivers, considering factors such as type of feeding, gender, parents' educational level and place of residence. Inductive and deductive methods were used to analyze the relationship between feeding practices and the nutritional status of infants. The results showed that inadequate complementary feeding practices prevail in a high percentage, significantly affecting nutritional status. It was found that 30% of the infants evaluated had some degree of malnutrition. In addition, patterns related to the mothers' level of schooling and rural residence were identified as influential factors. Therefore, it is essential to promote educational strategies aimed at caregivers in order to improve complementary feeding practices and reduce the prevalence of malnutrition in this vulnerable population.